ANALISA KUALITAS JARINGAN INTERNET WIRELESS LAN PADA JARINGAN LOKAL CV. BATAM JAYA WISATA MENGGUNAKAN METODE QOS (QUALITY OF SERVICE) - Panggabean, Wikaldo; Suharyanto, Cosmas Eko (Program Studi Sistem Informasi Institut Indobaru Nasional, 2024)
This study aims to determine the quality of service of the WLAN network in CV. Batam Jaya Tourism. QoS (Quality of Service) is the ability to provide information from computer networks in providing services to applications on the computer network so as to determine the level of satisfaction of users who use the network. This research is a quantitative research which refers to the research method according to Polit D.F and Hungler B.P. The research was carried out by monitoring the WLAN network at the access point which was determined as a sample in CV. Batam Jaya Wisata uses Axence netTools software. Data collection techniques used are observation, interviews, literature and monitoring. From the results of the research conducted, it can be concluded that the quality of service for the WLAN network in CV. Batam Jaya Wisata is included in the Satisfying category according to TIPHON.